Electoral violence during party primaries in Kenya. Issue 6 (18th August 2018) - Wanyama, Fredrick O.; Elklit, Jørgen
ABSTRACT: Since the restoration of multi-party democracy in Kenya in 1991, elections have witnessed intra-party violence during the primaries for selecting parliamentary and civic seats candidates. This article addresses the question of why electoral violence occurs during party primaries in Kenya and argues that violence is an outcome of the organization of political parties, which has revolved around personalities identified with ethno-regional interests rather than institutionalism. The upshot has been the absence of party institutionalization to establish structures for recruitment of members and organization of primaries. Such organizational weaknesses have denied parties the capacity to match the intense competition for tickets of ethno-regional dominant parties that guarantees nominees to win seats in their strongholds. Intra-party violence has followed. The article submits that intra-party electoral violence in Kenya is a function of the politics of clientelism and ethnicity, both of which have severely hampered the institutionalization of political parties and their capacity to cope with the stiff competition for the tickets of ethno-regional dominant parties.